1983
DOI: 10.1029/jc088ic06p03581
|View full text |Cite
|
Sign up to set email alerts
|

The global distribution of atmospheric carbon dioxide: 1. Aspects of observations and modeling

Abstract: A two‐dimensional global atmospheric transport model is used to relate estimated air to surface exchanges of CO2 to spatial and temporal variations of atmospheric concentration of CO2. This serves to illustrate the gross features of the carbon cycle and the measurement precision required of the burgeoning global observational network if the latter is to contribute useful information to the quantitative description of the cycle. Calculations are based on the atmospheric model coupled to a fixed, or variable dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

1984
1984
1993
1993

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 31 publications
2
41
0
Order By: Relevance
“…There is no evidence for a trend in this difference over the four years studied. The mean difference is less than the 4-5 ppm reported by Pearman et al (1983) based on an analysis of provisional data, but is not significantly different from that reported by Komhyr et al (1985a) and Pearman and Hyson (1986). The mean north-south difference is generally believed to be maintained by the emissions of fossil fuel CO?, primarily in midlatitudes of the northern hemisphere.…”
Section: Latitudinal Co? Distributionmentioning
confidence: 39%
See 2 more Smart Citations
“…There is no evidence for a trend in this difference over the four years studied. The mean difference is less than the 4-5 ppm reported by Pearman et al (1983) based on an analysis of provisional data, but is not significantly different from that reported by Komhyr et al (1985a) and Pearman and Hyson (1986). The mean north-south difference is generally believed to be maintained by the emissions of fossil fuel CO?, primarily in midlatitudes of the northern hemisphere.…”
Section: Latitudinal Co? Distributionmentioning
confidence: 39%
“…Previous studies have shown that this enhancement of -1 ppm in atmospheric COz results from a source of CO? in the equatorial oceans (Mook et al, 1983;Pearman et al, 1983;Pearman and Hyson, 1986). In the equatorial Pacific, the source is in an area of surface water highly ( -30%) supersaturated with CO,.…”
Section: Latitudinal Co? Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of time variations of C0 2 both in the atmosphere and in the sea surface layer have mostly been related to a seasonal or annual basis (Bolin and Keeling, 1963;Pearman et al, 1983;Takashi et al, 1983;Komhyr et al, 1985;Fushimi, 1987;Inoue et al, 1987;Peng et al, 1987). These large-scale temporal distributions have often been used to show the possible relations between changes in atmospheric C0 2 and sea surface temperature anomalies known as the El Nino phenomenon (Newell and Weare, 1977;Bacastow et al, 1980;Gammon et al, 1985;Elliot and Angel, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…The strengths of biologically plausible source variations were adjusted in a "trialand-error" fashion in an attempt to fit the concentration data. This approach has been extended by Pearman et al (1983) and Pearman and Hyson (1986). The limitation of the "forward-modelling" approach is that agreement between observed and calculated concentrations is only a weak test of the source model.…”
Section: Introductionmentioning
confidence: 99%